EBLIP5 Website Up and Running - Editorial Team (Evidence Based Library and Information Practice, 2007)
The University Library at Karolinska Institutet would like to welcome you to the 5th Evidence Based Library and Information Practice Conference in Stockholm, Sweden, June 29th - July 3rd 2009. Further details, including information about the venue and the conference organizers, can be found by visiting the new EBLIP5 website at http://eblip5.kib.ki.se.